Analysis of The Personality of The Characters in The Novel Dua Sides by Inggrida Tyas - Susanti, Aprilia; Rahayu, Sri (Universitas Negeri Semarang, 2025)
This research is motivated by the formation of the characters' personalities in the novel, which comes from the elements of reason and soul that can determine the behavior of each individual. Personality is part of the soul that builds human existence into a single unit, not divided into functions. Understanding personality means understanding me, the self, or understanding humanity as a whole. The whole personality consists of three major systems. They are called the id, ego, and superego. Research problems (1) How is the character's personality about the Id in the novel Dua Sisi by Inggrida Tyas? (2) How is the character's personality about Ego in the novel Dua Sisi by Inggrida Tyas? (3) How is the character's personality about the Superego in the novel Dua Sisi by Inggrida Tyas? This study specifically aims to determine and analyze the personality of the id, ego, and superego characters in the novel Dua Sisi by Inggrida Tyas. This research uses a qualitative approach with the content analysis method. This type of research uses library study research. The results showed that there are id, ego, and superego in the characters of Bisma, Kekasih, Bram, and Bunda, which were found in 118 data points. There are 42 data points of id personality, 25 of ego personality, and 51 of superego personality. The benefit of this research is to enrich the literature of the community's literary appreciation of the work of Saatra, and can also be used as a source of literary appreciation